Comparative effects of bioelectric and manual toothbrushing on acrylic denture teeth: Surface integrity and wear analysis - Luiz A. Pimenta; Carlos Nicolas Nowik; Salar Zeinali; Young Wook Kim (PLoS ONE, 2026)
Bioelectric toothbrushes deliver a low-level microcurrent intended to disrupt biofilm with reduced mechanical force, yet their effects on denture-tooth wear remain unclear. This in vitro study compared surface roughness and material loss of acrylic denture teeth brushed with a bioelectric toothbrush versus a soft-bristle manual toothbrush. Thirty-six heat-cured polymethylmethacrylate (PMMA) maxillary central incisors were randomly allocated to three groups (n = 12): manual brushing, bioelectric brushing without current (“OFF”), and bioelectric brushing with current (“ON”). Specimens underwent 20,000 brushing strokes (≈2 years of home cleaning) under a 200 g load using a brushing simulator in a 1:1 dentifrice/water slurry. Surface roughness (Ra, µm) and specimen weight (g) were recorded before and after brushing, and surface topography was qualitatively assessed by digital microscopy. Baseline roughness did not differ among groups (p > 0.05). After brushing, Ra increased significantly in the manual group (1.538 ± 0.219 to 2.233 ± 0.370 µm) and the bioelectric-OFF group (1.481 ± 0.199 to 2.157 ± 0.403 µm), whereas the bioelectric-ON group showed a smaller, non-significant change (1.547 ± 0.252 to 1.838 ± 0.197 µm); the bioelectric-ON condition resulted in significantly lower final roughness than the other groups (p < 0.05). No significant weight loss was detected in any group (p = 0.71). Microscopy corroborated profilometry, showing fewer and shallower scratches on specimens brushed with the bioelectric toothbrush in the ON mode. Within the limitations of this in vitro model, bioelectric activation was associated with reduced surface roughening of PMMA denture teeth without measurable material loss; however, clinical studies are needed to confirm its relevance under real-world oral conditions.